Terpenoids as principal bioactive compound of Cissampelos oppositifolia essential oils: enhancing synergistic efficacy with conventional antibiotics - Zhao, Kexin; Jiang, Yurong; Dev, Kamal; He, Xin; Sharma, Vipasha; Pang, Xinli (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundThe rise of antibiotic resistance imposes the search for novel antimicrobial strategies as natural products or its combination with antibiotics. This study investigates the synergistic effects of terpenoids from Cissampelos oppositifolia (C. oppositifolia) essential oil in combination with antibiotics against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). The aims were to evaluate the antimicrobial efficacy, analyze functional group modifications and assess molecular interaction.MethodsEssential oil was extracted from C. oppositifolia by hydro-distillation. The EO was analyzed for terpenoid content via Thin Layer Chromatography (TLC). Antimicrobial activity was assessed using the disc diffusion method and Minimum Inhibitory Concentration determinations (MIC) by broth dilution followed by bactericidal essay (Time-killing). FTIR and UV spectroscopy were employed to detect functional group modifications in terpenoid-antibiotic combinations. Molecular docking studies assessed interaction energies between terpenoids and antibiotics.ResultsTLC identified α-pinene, δ-carene, and caryophyllene in the EO. δ-Carene exhibited the highest synergy with antibiotics, showing the lowest MIC of 0.04 mg/mL against S. aureus ATCC-43300 and 0.05 mg/mL against E. coli MTCC-739. Time-kill assays demonstrated that α-pinene, δ-carene, and caryophyllene achieved complete bacterial eradication by 4 hours in combination with amoxicillin against E. coli, and by 2 hours against S. aureus in combination with erythromycin. FTIR analysis revealed peak shifts at 1599, 1774, and 2259 cm−1 for amoxicillin + α-pinene, and new peaks at 1648 and 1287 cm−1 for δ-carene + erythromycin. UV spectra indicated potential complex formations. Docking studies showed δ-carene’s strong interaction with erythromycin and amoxicillin, with interaction energies of -96.10 and -87.75 kcal/mol, respectively.ConclusionTerpenoids from C. oppositifolia enhance the antimicrobial efficacy of antibiotics. Functional group modifications and complex formations suggest that these interactions may contribute to synergistic effects. These findings support the potential use of terpenoid-antibiotic combinations in overcoming antibiotic resistance and warrant further investigation into their mechanisms of action.